1982
DOI: 10.1083/jcb.92.3.706
|View full text |Cite
|
Sign up to set email alerts
|

Immunological dissimilarity in protein component (dynein 1) between outer and inner arms within sea urchin sperm axonemes

Abstract: The 0.5 M KCI-treatment solubilizes the outer arms from sea urchin sperm axonemes. -30% of A-polypeptide, corresponding to dynein 1 in SDS-polyacrylamide gel, was solubilized by this treatment (as SEA-dynein 1) . Electron microscopic observation indicated that the extracted axonemes lacked the outer arms in various degrees. The SEA-dynein 1 was purified and an antiserum against it was prepared in rabbits. The specificity of antiserum to dynein 1 was determined by immunoelectrophoresis and Ouchterlony's double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Despite exhibiting the same 24-nm periodicities, the observed 3D structure of sea urchin o-SUB5-6 shows no indications that they are modified ODAs ( Figure 2 ; Movie S2 ). This feature is consistent with previous studies demonstrating that the o-SUB5-6 structures can not be decorated with antibodies against ODAs [69] , [70] . Previous studies have also observed that ODAs are almost completely missing from Chlamydomonas DMT1 [15] , [16] , [71] .…”
Section: Discussionsupporting
confidence: 93%
“…Despite exhibiting the same 24-nm periodicities, the observed 3D structure of sea urchin o-SUB5-6 shows no indications that they are modified ODAs ( Figure 2 ; Movie S2 ). This feature is consistent with previous studies demonstrating that the o-SUB5-6 structures can not be decorated with antibodies against ODAs [69] , [70] . Previous studies have also observed that ODAs are almost completely missing from Chlamydomonas DMT1 [15] , [16] , [71] .…”
Section: Discussionsupporting
confidence: 93%
“…In collaboration with Mohri and Ogawa, we found that the same antiserum also stained the spindle of rat-kangaroo PtK1 cells, as did another rabbit antidynein-1 prepared by Ogawa (18,19,31,32). Preliminary absorption experiments indicated that the fluorescence was due mainly to the presence of dynein-1 or a related antigen(s).…”
mentioning
confidence: 64%
“…Other reports have demonstrated that anti-sea urchin sperm flagella dynein 1 antibodies recognize the outer dynein arms of sea urchin sperm flagella by preembedding immunoelectron microscopy (Mohri et al, 1979;Ogawa et al, 1977Ogawa et al, , 1982. Postembedding immunoelectron microscopy of cilia or flagella has not yet been successful.…”
Section: Discussionmentioning
confidence: 99%